AB0160 Epigenetic Studies in Maternally versus Paternally Transmitted Psoriatic Disease. (10th June 2014) - O'Rielly, D.D.; Pollock, R.; Zhang, Y.; Al-Ghanim, N.; Yazdani, R.; Hamilton, S.; Bricknell, R.; Chandran, V.; Ardern, R.; Gladman, D.D.; Zhai, G.; Rahman, P.
Abstract : Background: Epidemiological studies have noted excess paternal transmission in psoriasis and psoriatic arthritis. To date, there has been no molecular explanation to account for this observation. Differential methylation patterns have long been implicated as a potential mechanism to account for excess paternal transmission. Objectives: In this pilot study, we investigated the differential methylation pattern among paternally and maternally transmitted PsA. Methods: Twenty-four (24) patients with maternally transmitted PsA were compared with 24 paternally transmitted PsA cases. For maternally transmitted PsA, the proband's mother had either psoriasis or PsA, and for paternally transmitted PsA, the proband's father had either psoriasis or PsA. Genome-wide DNA methylation profiling was performed on all these 48 samples by using Illumina HumanMethylation450k Beadchip, which measures up ∼480, 000 different CpG sites per sample and covers 96% of RefSeq genes. The methylation level at each CpG site was measured by β values varying from 0 (no methylation) to 1 (100% methylation). Results: Maternally transmitted PsA cases were predominantly females (19/24) with mean age of onset of PsA at 30.6 years. For paternally transmitted PsA, there were slightly more females (13/24) and age of onset of PsA was 22.2 years. Methylation data were normalized using BMIQ method and no batch effects were detected by PCA analysis. Methylation analysis was performed on 382, 024 of the 485, 512 CpG sites after filtering and revealed 90 significant CpG sites (p<0.05). The three most significant CpG sites were hypermethylated regions located on chromosome 8 that did not reside on or adjacent to a gene, with p values ranging from 9x10 –7 to 5x10 –6 . Many genes of interest based on current understanding of psoriatic disease were identified including hypermethylation of CPG sites on MICA (diff 10.22%; p=0.014), IRIF1 (diff 10.3%; p=0.016), PSORS1C3 (diff 11.1%; p=0.005); and TNFS4 (diff 15.2%; 0.004). Excess hypomethylation at CPG sites was noted on PSORS1C1 (18.9% diff. p=0.027). Conclusions: These preliminary results demonstrate that the global DNA methylation pattern in paternally transmitted PsA differs from maternally transmitted PsA. High priority candidate regions and genes identified in this study need further validation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3309